2020
DOI: 10.3389/fneur.2020.572850
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes in Tauopathies

Abstract: Tauopathies are a group of neurodegenerative diseases characterized by the progressive accumulation across the brain of hyperphosphorylated aggregates of the microtubule-associated protein tau that vary in isoform composition, structural conformation and localization. Tau aggregates are most commonly deposited within neurons but can show differential association with astrocytes, depending on the disease. Astrocytes, the most abundant neural cells in the brain, play a major role in synapse and neuronal function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 119 publications
1
45
0
Order By: Relevance
“…Tau can be classified as 3-repeat (3R) or 4-repeat (4R), corresponding to the number of repeat domains that result from alternative splicing of exon 10 of MAPT (8)(9)(10). In adults, the ratio of 3R to 4R tau is approximately 1:1; however, certain disease mutations in the MAPT gene can cause a change in the ratio of the isoforms toward greater expression of either 3R or 4R tau (11)(12)(13). Many primary genetic MAPT mutations are found in and around exon 10, resulting in tau mis-splicing, biased 4R tau production, or mutant tau protein expression (1,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Tau can be classified as 3-repeat (3R) or 4-repeat (4R), corresponding to the number of repeat domains that result from alternative splicing of exon 10 of MAPT (8)(9)(10). In adults, the ratio of 3R to 4R tau is approximately 1:1; however, certain disease mutations in the MAPT gene can cause a change in the ratio of the isoforms toward greater expression of either 3R or 4R tau (11)(12)(13). Many primary genetic MAPT mutations are found in and around exon 10, resulting in tau mis-splicing, biased 4R tau production, or mutant tau protein expression (1,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Pathological TauO triggers chronic neuroinflammation during AD, FTD, and many other tauopathies ( Guzman-Martinez et al, 2019 ; Nilson et al, 2017 ; Reid et al, 2020 ), and TauO accumulation in astrocytes may play a crucial role in pathological events ( Chun et al, 2020 ; González-Reyes et al, 2017 ; Reid et al, 2020 ). The effect of TauO on astrocytes and the underlying mechanism for TauO-induced aging-related neuroinflammation are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, studies have shown that astrocytes from aged mice are impaired to support neuronal growth and amyloid uptake and clearance, which leads to neurotoxicity accompanied by elevated neuroinflammatory molecules, thus contributing to progressive neuronal loss ( Iram et al, 2016 ; Kovacs, 2020 ). Chronic neuroinflammation and oxidative stress are observed in tauopathies; astrocytes seem to be involved in both, and TauO accumulation in astrocytes may play a crucial role in these pathological changes ( Chun et al, 2020 ; González-Reyes et al, 2017 ; Reid et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Astrocytes have been observed to internalize tau. However, it is yet unclear whether (or when) this internalization leads to degradation or propagation of tau, and whether this contributes to the induction of an inflammatory phenotype in astrocytes (Kovacs, 2020;Reid et al, 2020;Fleeman and Proctor, 2021). In AD, the presence of reactive astrocytes often precedes the formation of the disease's characteristic histopathologies (Heneka et al, 2005;Orre et al, 2014).…”
Section: Alzheimer's Diseasementioning
confidence: 99%